Análise das redes sociais informais com foco no fluxo da informação: estudo de caso em uma instituição financeira - Gontijo, Sandra Lúcia Silvestre da Cruz (2010)
This research had as objective to verify the contribution of the informal social nets in the flow of information inside of a bank agency. The used methodology was Analysis of Social Nets ARS, utilizing the software UCINET. The case study was accomplished through a research with 91% of the effective employees of the agency and it was divided in two phases: the first one with interviews including the whole team of employees and the second envolving just the managers of the area using the model of flow of information proposed by BEAL The findings confirmed that the flow of information does not depend on the formal structure. After having analyzed the information networks, both of friendship and of trust, besides the managers' egocentric nets, it was possible to identify structural aspects, as well as the actors, that play relevant roles in the net. The presented results don't confirm the relevance of all managers for the flow of information, besides of to unmask that several important actors in the net are informal leaders. The qualitative analysis also allowed emerging some bottlenecks that hinder the flow of the information and don't propitiate a favorable atmosphere to the knowledge management. The segmentation of the unit in three floors was pointed as the largest difficulty in the synergy and in the exchange of inputs among the team components. This was evident when was realized the analysis of the four nets in each floor. So, the methodology of analysis of social nets was pointed as a capable tool to reveal what is not in the organization chart, nor in the formal leaders' speech, representing these aspects just the occult part of the iceberg